Efficacy of the Kombucha Beverage Derived from Green, Black, and Pu’er Teas on Chemical Profile and Antioxidant Activity - Yi Hsieh; Ming-Chung Chiu; Jui-Yu Chou (Journal of Food Quality)
Kombucha is a symbiotic culture of bacteria and yeast which produces a high-end fruity fitness beverage by fermentation of normal tea for approximately two weeks. In addition to the advantage of being a low-sugar probiotic-rich drink, kombucha also offers the benefits of the tea used for its preparation, especially its high antioxidant content. In this research, kombucha tea was prepared by using three different tea types: green, black, and pu’er tea, and the chemical profiles and antioxidant activity were analyzed during the fermentation process (up to 20 days). The results showed that the tea type has an obvious influence on the factors associated with the antioxidant potential. The fermentation process caused a marked increase in polyphenol content and antioxidant activity initially, but this slowed progressively over time. In contrast, the fermentation of black tea contributed to the degradation of flavonoids but showed no significant effect on the other tea types. Therefore, we conclude that the tea type selected to make kombucha affects the end product as well as the fermentation time.